Molecular targeted therapies for pediatric atypical teratoid/rhabdoid tumors - Chang Zhang; Hao Li (Wiley, 2022)
ABSTRACT Atypical teratoid/rhabdoid tumors (AT/RTs) are lethal central nervous system tumors, which are primarily diagnosed in infants. Current treatments for AT/RTs include surgery, radiotherapy, and chemotherapy; these treatments have poor prognoses and challenging side effects. The pivotal genetic event in AT/RT pathogenesis comprises the inactivation of SMARCB1 or SMARCA4. Recent epigenetic studies have demonstrated mutual and subtype‐specific epigenetic derangements that drive tumorigenesis; the exploitation of these potential targets might improve the dismal treatment outcomes of AT/RTs. This review aims to summarize the literature concerning targeted molecular therapies for pediatric AT/RTs.